Analisa Kestabilan Lereng Menggunakan Metode Fellenius Secara Manual dan Software Slide Rocscience 6.0 (Studi Kasus : TB 1.42 Pemali PT Timah (Persero) Tbk: Analysis Slope Stability Using Fellenius Method Manually And Software Slide Rocscience 6.0 in TB 1.42 Pemali PT Timah (Persero) Tbk - Tiambunan, Damos; Irvani, Irvani; Fahraini, Ferra (Program Studi Teknik Pertambangan Universitas Bangka Belitung, 2018)
A hill slope is a part of a mining, especially mining by Open Pit Method. The TB 1.42 Pemali PT Timah (Persero)Tbk, which is often referred as the TB 1.42 applies the open it method in its mining, hence the condition of the hill slope greatly influences the mining Safety because hill slope instability can cause avalance. Hance, the hill slope stability has to be calculated.The calculation is performed to get the value of the safety factor (FK) and to understand the slope’s condition. This calculation can be done using yheFelleniusMethod, either manually or using,SoftwareSlideRocscience 6.0. The FelleniusMethod requires the shear strength parameter in the calculation, therefore a laboratory testing is performed using direct shear test ASTM D-3064-04. This test generates the value of cohesion (c),the angle of internal friction (ɸ) and the soil density (γ) of a soil sample taken from the field.Basedon the research the front south slope TB 1.42 Pemali have sandy loam lithology (Slope LT01), clay (Slope LT02 dan LT03), and gravelly clay (slope LT04). Based on the Fellenius Method, the value of FK for the slope is affected by the slope’s angle and shear strength parameter ( c and ɸ). The analysis conducted in this study showed that of the four slopes that are observed, there are two unstable slopes, which are slope LT02 with FK amounted to 0,809 (manual) and 0,877 (slide), which is unstable ; and the slope LT03 with FK amounted to 1,056 (manual) and 1,070 (slide), which is in critical condition. In order to solve the instability of the slope, PT Timah (Persero) Tbk. Can alter the slope’s geometry and install a grouted tieback anchors at unstable slopes.